Interferon-γ and Systemic Autoimmunity - Pollard, K.M. (2013)
The term interferon describes a family of proteins consisting of three major types (I, II, III) which differ in their primary protein sequences, cognate receptors, genetic loci, and cell types responsible for their production. The interferons, especially types I and II, overlap significantly in the genes they control resulting in a shared spectrum of diverse biological effects which includes regulation of both the innate and adaptive immune responses. As such, the interferons are major effectors in the pathogenesis of autoimmunity, especially systemic autoimmunity. The type I IFNs, because they are produced during the early stages of the innate immune response, are thought to play the foremost role in autoimmune responses. However, numerous studies have found that the single type II IFN, IFN-γ, plays an essential role in the development and severity of systemic autoimmunity, particularly systemic lupus erythematosus. This is supported by animal studies where IFN-γ is uniformly required in both spontaneous and induced models of lupus. Although expression of IFN-γ in cells of the innate immune system is almost immediate after activation, expression in adaptive immunity requires a complex orchestration of cellular interactions, signaling events and epigenetic modifications. The multifaceted nature of IFN-γ in adaptive immunity identifies numerous possible therapeutic targets that, because of the essential contribution of IFN-γ to systemic autoimmunity, have the potential for producing significant benefits.